The Anti-Depression-Like Effects of Zhengtian Capsule via Induction of Neurogenesis and the Neurotrophic Signaling Pathway - Yang, Liang; Wang, Yong; Li, Nuomin; Xu, Bing; Duan, Juanhui; Yuan, Chunxu; Yuan, Qinfen; Yang, Qifan; Qing, Hong; Dai, Zhi; Quan, Zhenzhen (Frontiers in Pharmacology, 2020)
Background Oxidative stress that causes nerve damages in neurodegenerative disease has been widely studied for the pathogenesis and diagnostic measures. Zhengtian capsules (ZTC), a type of traditional Chinese medicine for headaches, has been found to have extra effects in recent years, such as increasing the level of serotonin and dopamine in the brain, but its specific mechanism has not been clearly elucidated. Aims In this study, we focused on revealing whether ZTC can regulate key proteins of neurotrophic signaling pathway to alleviate depression like behavior caused by oxidative stress. methods The effects of ZTC on LPS induced oxidative stress were analyzed by behavioral experiments, immunofluorescence histochemical experiments, Western blot and RT-qPCR. Outcomes We mainly tested the regulatory effect of ZTC on BDNF and hippocampal neurogenesis in LPS model mice. Experimental results show that the doses of ZTC (M 0.34 g / kg, and H 0.7 g / kg) can elevate the proliferation of neural stem cells and GABAergic-type neurons in the hippocampus, promote the protein levels of BDNF, phosphorylated ERK1/2 and CERB, and inhibit the expression level of an inflammation factor NFκB. Conclusion These data suggest ZTC acts on multiple ways to resist excessive oxidative stress, proving it to be a potential neurotrophic drug.